When Labor Disputes Bring Cities to a Standstill: The Impact of Public Transit Strikes on Traffic, Accidents, Air Pollution, and Health - Stefan Bauernschuster; Timo Hener; Helmut Rainer (Center for Economic Studies and ifo Institute (CESifo), 2015)
Many governments have banned strikes in public transportation. Whether this can be justified depends on whether strikes endanger public safety or health. We use time-series and cross-sectional variation in powerful registry data to quantify the effects of public transit strikes on urban populations in Germany. Due to higher traffic volumes and longer travel times, total car hours operated increase by 15% during strikes. This effect is accompanied by a 14% increase in vehicle crashes, a 20% increase in accident-related injuries, a 14% increase in particle pollution, and an 11% increase in hospital admissions for respiratory diseases among young children.
Keywords: L91; R41; Q53; I18; 330; public transit; strikes; traffic; air pollution; health